Temperature and Soil Moisture Stress Modulate the Host Defense Response in Chickpea During Dry Root Rot Incidence - Sharath Chandran, U. S.; Tarafdar, Avijit; Mahesha, H. S.; Sharma, Mamta (Frontiers in Plant Science, 2021)
Dry root rot caused by the necrotrophic phytopathogenic fungus Rhizoctonia bataticola is an emerging threat to chickpea production in India. In the near future, the expected increase in average temperature and inconsistent rainfall patterns resultant of changing climatic scenarios are strongly believed to exacerbate the disease to epidemic proportions. The present study aims to quantify the collective role of temperature and soil moisture content (SMC) on disease progression in chickpea under controlled environmental conditions. In our study, we could find that both temperature and soil moisture played a decisive role in influencing the dry root rot disease scenario. As per the disease susceptibility index (DSI), a combination of high temperature (35°C) and low SMC (60%) was found to elicit the highest disease susceptibility in chickpea. High pathogen colonization was realized in chickpea root tissue at all time-points irrespective of genotype, temperature, and SMC. Interestingly, this was in contrast to the DSI where no visible symptoms were recorded in the roots or foliage during the initial time-points. For each time-point, the colonization was slightly higher at 35°C than 25°C, while the same did not vary significantly with respect to SMC. Furthermore, the differential expression study revealed the involvement of host defense-related genes like endochitinase and PR-3-type chitinase (CHI III) genes in delaying the dry root rot (DRR) disease progression in chickpea. Such genes were found to be highly active during the early stages of infection especially under low SMC.